Photoredox‐Catalyzed Reductive Coupling of Aldehydes, Ketones, and Imines with Visible Light. Issue 30 (17th June 2015) - Nakajima, Masaki; Fava, Eleonora; Loescher, Sebastian; Jiang, Zhen; Rueping, Magnus
Abstract Ketyl radical and amino radical anions, valuable reactive intermediates for CC bond‐forming reactions, are accessible through a CO/CNR umpolung. However, their utilization in catalysis remains largely underdeveloped owing to the high reduction potential of carbonyl compounds and imines. In the context of photoredox catalysis, tertiary amines are commonly employed as sacrificial co‐reducing agents. Herein, an additional role of the amine is proposed, in which it is essential for the organocatalytic substrate activation. The combination of photoredox catalysis and carbonyl/imine activation enables the reductive coupling of aldehydes, ketones, and imines under mild reaction conditions.